Shatterproof - Smith, Roland, 1951- (39 clues. Cahills vs. Vespers, 2012)
Vesper One commands Dan and Amy Cahill to steal the Golden Jubilee, one of the world's largest diamonds, but what they do not know is that the Jubilee theft is just a setup and someone is going to die.